Business Models For Electronic Commerce - A Case Study Of Malaysia Websites - K.K.Nair, Vijaya Kumaran (2000)
This report attempts to clarify terminology discussing the interface between commerce and the Internet. It is also a classification system or taxonomy of existing Internet business models. The latter part of the paper discusses the role of business, goverments, regulation and ideology in the development of E-commerce and makes some cautions speculating regarding its future.